Effects of thiamine, pyridoxine, pantothen acid, and riboflavin on growth performance, feed efficiency, and body composition of seabass, lates calcarifer (Bloch) - Mali Boonyaratpalin (Prince of Songkla University, 2024)
Seabass (Lates calcarifer) of initial average weight 0.45-0.47 gm. were experimentally reared in 200 1.glass aquaria fitted with a closed recirculating system. The experiment comprised 6 treatments with 3 replications each. Six diet formulae were used; 1) minced fish; 2) minced fish supplemented with complete vitamins and minerals; 3),4),5) and 6) same as that of formula 2 but deficient in thiamine, pyridoxine, pantothenic acid and riboflavin, respectively. After rearing for 6 weeks ,results appeared the fish in treatment 1 (minced fish alone) had developed the deficiency symptoms, and revealed the lowest value of growth. A study of recovery proved that fish fed basal diet incorporated with complete vitamin showed better growth and other parameters i.e. feeding rate, FCR and body composition than the other group (as given minced fish alone). Fish in treatment 2-6 gave an insignificant different on average body weight among them, but showed some anomali after rearing for 8 weeks i.e. fish in treatments 3 (thiamine deficiency) and 5 (pantothenic acid deficiency) 1M.S. (Fisheries) 2M.S. (Marine Zoology) Ph.D. (Aquatic Biology), Dept.of Aquatic Science,Fac of Natural Resources Prince of Songkla Univer., THAILAND, 90110.